Recent advances in exploring and exploiting soybean functional peptides—a review - Zhu, Yongsheng; Chen, Gang; Diao, Jingjing; Wang, Changyuan (Frontiers in Nutrition, 2023)
Soybeans are rich in proteins and phytochemicals such as isoflavones and phenolic compounds. It is an excellent source of peptides with numerous biological functions, including anti-inflammatory, anticancer, and antidiabetic activities. Soy bioactive peptides are small building blocks of proteins that are released after fermentation or gastrointestinal digestion as well as by food processing through enzymatic hydrolysis, often in combination with novel food processing techniques (i.e., microwave, ultrasound, and high-pressure homogenization), which are associated with numerous health benefits. Various studies have reported the potential health benefits of soybean-derived functional peptides, which have made them a great substitute for many chemical-based functional elements in foods and pharmaceutical products for a healthy lifestyle. This review provides unprecedented and up-to-date insights into the role of soybean peptides in various diseases and metabolic disorders, ranging from diabetes and hypertension to neurodegenerative disorders and viral infections with mechanisms were discussed. In addition, we discuss all the known techniques, including conventional and emerging approaches, for the prediction of active soybean peptides. Finally, real-life applications of soybean peptides as functional entities in food and pharmaceutical products are discussed.